2014
DOI: 10.1080/19476337.2014.917336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transglutaminase additive on the quality of gluten-free bread

Abstract: The aim of the work was to determine the impact of addition of transglutaminase (TGase), soy and whey protein on physicochemical and sensory properties of gluten-free breads. Samples were produced from concentrates consist of 7% of soy or whey protein. TGase was added in amount of 1, and 10 U/g of protein. Following features have been marked for each gluten-free bread sample: specific mass, specific volume, crumb porosity, moisture and crumb hardness. One observed that more valuable changes have been observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…Recent scientific studies have increasingly focused on GFB (Dłużewska, Marciniak-Lukasiak, & Kurek, 2015;Różyło, Rudy, Krzykowski, & Dziki, 2015;Różyło, Rudy, Krzykowski, Dziki, Gawlik-Dziki et al, 2015;Tsatsaragkou et al, 2014). GFB is unaccepted completely by consumers (Mariotti, Pagani, & Lucisano, 2013), because many studies have addressed the impact of various additives on the quality of GFB.…”
Section: Introductionmentioning
confidence: 99%
“…Recent scientific studies have increasingly focused on GFB (Dłużewska, Marciniak-Lukasiak, & Kurek, 2015;Różyło, Rudy, Krzykowski, & Dziki, 2015;Różyło, Rudy, Krzykowski, Dziki, Gawlik-Dziki et al, 2015;Tsatsaragkou et al, 2014). GFB is unaccepted completely by consumers (Mariotti, Pagani, & Lucisano, 2013), because many studies have addressed the impact of various additives on the quality of GFB.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of soy protein isolate to amadumbe flour would improve the composite’s amino acid content. Transglutaminase has been proposed to form cross‐links by catalysing an acyl transfer reaction between a γ‐carboxy amide of the peptide or protein‐bound glutamine and a primary amine (Babiker et al , ; Dłużewska et al , ). The presence of glutamine and lysine in the flours confirms them as potential sources of substrates for modification.…”
Section: Resultsmentioning
confidence: 99%
“…to 0.75% in the samples had a negative effect on bread hardness (Dłużewska et al, 2015). Onyango, Mutungi, Unbehend, and Lindhauer (2010) showed that adding the concentration of enzyme lowered rheology, while viscosity and elastic return were increased.…”
Section: Hardnessmentioning
confidence: 96%
“…According to Dłużewska et al (2015), adding TGase (1 U/g) increased the SpVol and porosity of the product. However, the changes were not significant.…”
Section: Spvolmentioning
confidence: 99%